RELATIONSHIP BETWEEN BODY COMPOSITION AND MAXIMUM OXYGEN VOLUME (VO2MAX) IN YOUNG AND YOUNG ADULT MALE ATHLETES (10-30 YEARS OLD - Sari, Aria Novita (Jurnal Pendidikan Olah Raga, 2019)
Physiologically, male athletes have less body fat and higher muscle mass than women athletes. These conditions make male athletes more easier to regulate oxygen (O2) consumption to muscles, to support maximum performance during exercising. Physical fitness athlete is related to the ability hit peak performance. The average of ability hit peak performance is < 30 years old. Maximal oxygen uptake (vo2max) has been regarded as the best indicator of athlete's physical capacity. The purpose of this systematic review was to determine relationship between body composition with vo2max in young and young adult athletes (10-30 years old). The method used is a systematic review, articles were searched by ProQuest, Wiley Online Library, and ScienceDirect database. There are five articles that meet the inclusion and exclusion criteria. Body compositions observed include BMI, BM, LBM, BF, and FM. The results obtained by IMT was significant negative (r -0.42), (r -0.39), (r -0.36). BM was significant negative (r -0.39). LBM was significant positive (r 0.51), (r 0.38), and (r 0.38). % BF was significant negative (OR -0.804) and (r -0.40). FM was significant negative (r -0.36) and (r -0.36).